Investigating the response of biotite to impact metamorphism: Examples from the Steen River impact structure, Canada. (27th November 2017) - Walton, E. L.; Sharp, T. G.; Hu, J.; Tschauner, O.
Abstract: Impact metamorphic effects from quartz and feldspar and to a lesser extent olivine and pyroxene have been studied in detail. Comparatively, studies documenting shock effects in other minerals, such as double chain inosilicates, phyllosilicates, carbonates, and sulfates, are lacking. In this study, we investigate impact metamorphism recorded in crystalline basement rocks from the Steen River impact structure (SRIS), a 25 km diameter complex crater in NW Alberta, Canada. An array of advanced analytical techniques was used to characterize the breakdown of biotite in two distinct settings: along the margins of localized regions of shock melting and within granitic target rocks entrained as clasts in a breccia. In response to elevated temperature gradients along shock vein margins, biotite transformed at high pressure to an almandine‐Ca/Fe majorite‐rich garnet with a density of 4.2 g cm −3 . The shock‐produced garnets are poikilitic, with oxide and silicate glass inclusions. Areas interstitial to garnets are vesiculated, in support of models for the formation of shock veins via oscillatory slip, with deformation continuing during pressure release. Biotite within granitic clasts entrained within the hot breccia matrix thermally decomposed at ambient pressure to produce a fine‐grained mineral assemblage of orthopyroxene + sanidine + titanomagnetite. These minerals are aligned to the (001) cleavage plane of the original crystal. In this and previous work, the transformation of an inosilicate (pargasite) and a phyllosilicate (biotite) to form garnet, an easily identifiable, robust mineral, has been documented. We contend that in deeply eroded astroblemes, high‐pressure minerals that form within or in the environs of shock veins may serve as one of the possibly few surviving indicators of impact metamorphism.